Poly(2-Hydroxyethyl Methacrylate) Hydrogel-Based Microneedles for Bioactive Release - Sharma, Manoj B.; Abdelmohsen, Hend A. M.; Kap, Özlem; Kilic, Volkan; Horzum, Nesrin; Cheneler, David; Hardy, John G. (Bioengineering (Basel), 2024)
Microneedle arrays are minimally invasive devices that have been extensively investigated for the transdermal/intradermal delivery of drugs/bioactives. Here, we demonstrate the release of bioactive molecules (estradiol, melatonin and meropenem) from poly(2-hydroxyethyl methacrylate), pHEMA, hydrogel-based microneedle patches in vitro. The pHEMA hydrogel microneedles had mechanical properties that were sufficiently robust to penetrate soft tissues (exemplified here by phantom tissues). The bioactive release from the pHEMA hydrogel-based microneedles was fitted to various models (e.g., zero order, first order, second order). Such pHEMA microneedles have potential application in the transdermal delivery of bioactives (exemplified here by estradiol, melatonin and meropenem) for the treatment of various conditions.